Evaluation of performance variables to accelerate the deployment of sustainable aviation fuels at a regional scale. (1st January 2023) - Bhatt, Arpit H.; Zhang, Yimin; Milbrandt, Anelia; Newes, Emily; Moriarty, Kristi; Klein, Bruno; Tao, Ling
Highlights: Implications of key performance variables on the deployment of SAF is assessed. Feedstocks are available to displace up to 55% of Chicago airport's jet fuel with SAF. SAF is cost competitive with Jet A for several ASTM technology pathways. Lifecycle GHG emissions could be reduced up to 86% compared to Jet A by using SAF. Feedstock cost & renewable fuel incentive are key cost drivers impacting SAF costs. Abstract: An increase in jet fuel consumption and its associated emissions across the world have led to the need for alternative technologies to produce sustainable aviation fuels (SAF). One option to produce SAFs is to utilize waste or biomass-based feedstocks that has the potential to reduce greenhouse gas emissions by 50% or more compared to conventional jet fuel. However, there is a lack of understanding of how the synergistic effects of key performance variables could hinder or help the deployment of aviation fuels on a regional scale. Here, we assess the implications of key variables–including type and quantity of waste/biomass feedstock availability near the airport, cost of SAF production, life cycle greenhouse gas (GHG) emissions, policies, and fuel/infrastructure logistics–on the deployment of SAF at Chicago's O'Hare International Airport. We consider three ASTM International-approved SAF technologies (Hydroprocessed Esters and Fatty Acids, Fischer-Tropsch, and Alcohol to Jet) that can be blended up to 50% with petroleum-based jet fuel. Results from our analysis show that woody biomass-based Fischer-Tropsch technology has the lowest fuel production costs (2.31–2.81/gallon gasoline equivalent) of all pathways, and it reduces life cycle GHG emissions by 86% compared to conventional jet fuel despite the higher availability of crop residues compared to either woody biomass or fats, oils, and greases. Also, infrastructure is available at O'Hare International Airport to blend SAF with Jet A fuel through three terminals directly connected to the airport via pipelines. Our sensitivity analysis shows renewable fuel incentives and feedstock price to be key performance variables affecting the production cost and deployment of SAF.